Benefit of N-Acetylcysteine in Postoperative Hepatic Dysfunction: Case Report and Review of Literature - Deanna K. Bauerlein; Hashem N. Akbar; Erik C. von Rosenvinge; Nora D. Loughry; Preeti R. John (Case Reports in Hepatology)
N-Acetylcysteine (NAC) is reported to have multiple clinical applications in addition to being the specific antidote for acetaminophen toxicity. NAC stimulates glutathione biosynthesis, promotes detoxification, and acts directly as a scavenger of free radicals. It is a powerful antioxidant and a potential treatment option for diseases characterized by the generation of free oxygen radicals. We present a case of postoperative hepatic dysfunction of multifactorial etiology in a patient with therapeutic acetaminophen levels, where hepatic function improved considerably following administration of intravenous NAC. This case suggests that NAC should be considered for treatment of acute liver dysfunction in the postoperative setting, even in the absence of elevated acetaminophen levels.